TREATMENT OF STEROID-RESISTANT RENAL-ALLOGRAFT REJECTION WITH OKT-3 AND PLASMAPHERESIS - HABERAL, M; BULUT, O; SERT, S; GULAY, H; ARSLAN, G; GUNGEN, Y; HAMALOGLU, E; ALTUNKAN, S; BILGIN, N (MARCEL DEKKER INC, 1991)
The murine monoclonal antibody (OKT-3) and plasmapheresis therapy were applied in combination to treat acute renal allograft rejection in 31 patients who were not responsive to conventional bolus steroid treatment. Six of them were living related but ABO incompatible; another 25 patients were ABO compatible (1 was from a cadaver, 7 were from living unrelated donors, and 17 were from living related donors). Of these 31 patients, 25 (80.65%) showed perfect improvement in their graft function. These 25 patients had a mean follow-up time of 8 months, and had mean creatinine values of 1.2 mg % (0.8-2.8 mg %). It is concluded that OKT-3 and plasmapheresis combination therapy is very effective in reversing steroid-resistant rejections in high-risk patients such as ABO-incompatible cases.
Keywords: OKT3; PLASMAPHERESIS, REJECTION; RENAL TRANSPLANTATION; Urology & Nephrology